Key success factors of health maintainance organizations in Singapore. - Chao, Zhang Qi. (2008)
In the early nineties, the health care industry in Singapore was faced with rising health care cost, leading to the setup of managed care schemes, of which NTUC MHS was one of the pioneers (Chong 2003). Following NTUC MHS, there was a proliferation of schemes over the years by Aviva Pte Ltd, Raffles Medical Group Ltd, Parkway Shenton Healthnet, Gethin-Jones Medical Practice Pte Ltd and Managed Health care Group (MHC). In this study, through our interviews with their senior executive management and physicians, we seek to identify the key success factors that drive these organizations forward. Our research shows that: (1) An advanced IT system, (2) Critical Mass, (3) Flexibility of plan design, (4) Access to care by Location and (5) Physician Satisfaction are the factors critical for the success of HMOs in Singapore. Lastly, we discuss how a managed health care organization can use a balanced scorecard approach to integrate and incorporate these key success factors.